How Is the Probability of Reporting Various Levels of Pain 12 Months After Noncatastrophic Injuries Associated with the Level of Peritraumatic Distress?. Issue 2 (February 2022) - Modarresi, Shirin; MacDermid, Joy C.; Suh, Nina; Elliott, James M.; Walton, David M.
Abstract: Background: Psychological factors have been shown to be consistent predictors of chronic pain in people with musculoskeletal injuries. However, few prognostic studies have considered multiple risk factors including peritraumatic distress. In addition, previous research has not considered that the associations between peritraumatic distress and pain levels can vary across pain outcomes. Question/purpose: To determine whether an easily measurable level of baseline distress is associated with pain levels 1 year after noncatastrophic traumatic injuries when the outcome to be assessed is not normally distributed. Methods: This was a prospective cohort study. The data were captured from two cohorts in London, Ontario, Canada, and Chicago, IL, USA. Participants were adults with acute noncatastrophic (that is, not treated with surgery or hospitalization) musculoskeletal injuries of any etiology with various injury locations (60% [145 of 241] spinal and 40% [96 of 241] peripheral) that presented to local urgent care centers. Other inclusion criteria included English/French speakers and having no other disorder that would affect their pain levels. In total, between the years 2015 and 2018, 241 participants were recruited based on the inclusion criteria. Ninety-three percent (225 of 241) of participants provided baseline data, and of these, 48% (109 of 225) were lost to follow-up in 1 year. Based on a complete case approach, this study included 116 participants who ranged in age from 18 to 66 years and 69% (80) of whom were women. The Traumatic Injuries Distress Scale (TIDS) was used to evaluate distress at baseline (within 4 weeks of injury). The TIDS is a validated, reliable 12-item risk prognosis screening tool that takes less than 3 minutes to complete with questions regarding uncontrolled pain, negative affect, and intrusion/hyperarousal. The minimum and maximum possible scores are 0 and 24, with higher scores indicating higher levels of distress. The Numeric Pain Rating Scale (NPRS) was used to assess the pain level at baseline and again 12 months postinjury. To complete the NPRS, participants rate the severity of their pain on a scale of 0 to 10, with 0 indicating no pain and 10 indicating the worst pain imaginable. NPRS scores of 1 to 3 indicate mild pain, 4 to 6 indicate moderate pain and 7 or higher indicate severe pain. As a preliminary analysis, to assess whether the participants as a group experienced recovery, a paired samples t-test was used to compare NPRS scores at baseline and 12 months. In all, 52% (60 of 116) of participants reported no pain (NPRS = 0), and mean pain intensity scores improved from 4.8 ± 2.1 at baseline to 1.6 ± 1.6 at 12-month follow-up (p < 0.001). Quantile regression was used to describe the association between baseline distress and pain levels 1 year after the injury. This technique was used because it reveals the relationships at different quantiles of the pain outcome distribution. Results: The results indicate some people (52% [60 of 116]) recovered regardless of their baseline level of distress (30 th quantile of the NPRS: β = 0). However, in those with persisting pain, higher levels of baseline distress are associated with greater levels of pain 12 months after the injury (50 th quantile of the NPRS: β = 0.11; p = 0.01; 70 th quantile of the NPRS: β = 0.27; p < 0.001; 90 th quantile of the NPRS: β = 0.31; p = 0.01). According to this model, with a baseline TIDS score of 5, there is 10% probability that patients will report moderate or greater levels of pain (4 or higher of 10) 12 months later. This probability then increases as the TIDS score increases. For instance, at a score of 13 on the TIDS, the probability of a patient reporting moderate or higher levels of pain increases to 30%, and the probability of reporting severe pain (higher than 6 of 10) is 10%. Conclusion: Clinicians and surgeons in orthopaedic settings can screen for the presence of peritraumatic distress using the TIDS, which is an easily administered tool that does not require extensive knowledge of psychology, and by using it they can identify those with higher levels of distress who are more likely to have persistent, long-term pain. A score of 4 or less indicates a low risk of persistent pain, a score between 5 and 12 (endpoints included) indicates moderate risk, and a score of 13 or higher indicates high risk. Future studies should investigate whether certain immediate interventions for peritraumatic distress in the aftermath of trauma can decrease the likelihood that a patient will develop chronic pain after injury. As an analysis technique, quantile regression is useful to assess complex associations in many orthopaedic settings in which a certain outcome is expected to occur in most patients leading to non-normally distributed data. Level of Evidence: Level II, therapeutic study.